Perilaku Agresi dalam Film Misumisou Karya Sutradara Eisuke Naito - Maghfira, Ahlani; Puspitasari, Diana; Kadafi, Muammar (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
This study discusses aggressiveness in Misumisou, the film directed by Eisuke Naito.  This study aims to determine the forms of aggressions of the characters Nozaki Haruka, Aiba Mitsuru, Sayama Rumi, and Oguro Taeko in the film based on the motivation of their behavior using Erich Fromm's aggression perspective.  This research type is qualitative research using note-taking method.  The results of this research showed that the form of violence perpetrated by: 1) Nozaki Haruka, was vengeful destructiveness behavior due to revenge, and defensive aggression as response of fear and physical threats 2) Aiba Mitsuru, was sadistic aggression, driven by an unfulfilled “effectiveness” desire.  3) Sayama Rumi, was sadistic aggression, driven by her wounded narcissism desire.  4) Oguro Taeko, was sadistic aggression driven by her thwarted desire for freedom, and defensive aggression in response to the threat of physical attack. Types of aggressions are classificated by someone’s motive that based on individual’s character.